2000
DOI: 10.1086/312733
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Spatial and Spectral Structure in the X-Ray Emission from the Crab Nebula

Abstract: The Chandra X-Ray Observatory observed the Crab Nebula and pulsar during orbital calibration. Zeroth-order images with the High-Energy Transmission Grating (HETG) readout by the Advanced CCD Imaging Spectrometer spectroscopy array (ACIS-S) show a striking richness of X-ray structure at a resolution comparable to that of the best ground-based visible-light observations. The HETG-ACIS-S images reveal, for the first time, an X-ray inner ring within the X-ray torus, the suggestion of a hollow-tube structure for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
426
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(460 citation statements)
references
References 19 publications
(46 reference statements)
34
426
0
Order By: Relevance
“…Taking into account the above properties of the pulsar wind, the observed morphology of PWNe, and first of all the characteristic disk-jet structure (Weisskopf et al 2000;Gaensler and Slane 2006), is naturally explained (Lyubarsky 2002). Namely, the disk is formed by the relatively weakly magnetized equatorial flow, which transfers most of the energy.…”
Section: General Properties Of Pulsar Winds and Structure Of Pwnementioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account the above properties of the pulsar wind, the observed morphology of PWNe, and first of all the characteristic disk-jet structure (Weisskopf et al 2000;Gaensler and Slane 2006), is naturally explained (Lyubarsky 2002). Namely, the disk is formed by the relatively weakly magnetized equatorial flow, which transfers most of the energy.…”
Section: General Properties Of Pulsar Winds and Structure Of Pwnementioning
confidence: 99%
“…However, it was not until the Hubble Space Telescope (HST; Hester et al 1995) and Chandra (Weisskopf et al 2000) era when the intricate and complex structure of the nebula was revealed (see Figure 1 for the feature nomenclature introduced by Hester et al 1995). These observations have also shown that the bright inner part of the nebula is very dynamic, with apparent velocities corresponding to up to 0.5c (in projection onto the sky) as measured, e.g., from the shifts in wisp positions (Hester et al 2002).…”
Section: Multiwavelength Properties Of the Crabmentioning
confidence: 99%
“…In the last decade, thanks to the unprecedented imaging power of Chandra, high resolution observations of the inner region of the CN have become available also in the X-ray band, revealing a striking jet-torus structure, knots and rings (Weisskopf et al 2000), previously just barely inferred (Brinkmann et al 1985;Hester 1995). These observations prompted a theoretical effort at modelling PWNe, and the CN in particular, within the framework of time-dependent multi-D MHD.…”
Section: Introductionmentioning
confidence: 99%
“…Fine X-ray images taken with the Chandra X-ray Observatory have brought a renaissance to the structural study of the Crab nebula and other pulsar wind nebulae (see Weisskopf et al [59] and references given in a review by Arons [60]). The discovery of two concentric torii is one of the many key observations brought forward by Chandra.…”
Section: Crab Nebulamentioning
confidence: 99%